2020
DOI: 10.1039/d0qo00698j
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in the transition-metal-free synthesis of heterocycles from alkynoates: an overview and current status

Abstract: This review highlights the successful utilization of transition-metal-free approaches for the modular assembly of various heterocycles from alkynoates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 378 publications
(294 reference statements)
0
17
0
Order By: Relevance
“…The optimization studies revealed that the solvent severely influenced the cyclization reaction whereas dichloroethane and acetonitrile gave the product in lower yields than dichloromethane, while toluene and ethanol did not afford the product. The use of tetrahydrofuran led to the appearance of a product with the same molecular weight as the benzoimidazolo thiazine 3 a, which was identified as benzothiazolo imidazole 4 a, while dimethylformamide afforded exclusively 4 a in 69% yield (Table 1, entries [18][19][20][21][22][23]. The effect of dry systems (nitrogen atmosphere) versus those run in an open atmosphere was also tested and a similar rate of reaction was obtained (Table 1, entry 25).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The optimization studies revealed that the solvent severely influenced the cyclization reaction whereas dichloroethane and acetonitrile gave the product in lower yields than dichloromethane, while toluene and ethanol did not afford the product. The use of tetrahydrofuran led to the appearance of a product with the same molecular weight as the benzoimidazolo thiazine 3 a, which was identified as benzothiazolo imidazole 4 a, while dimethylformamide afforded exclusively 4 a in 69% yield (Table 1, entries [18][19][20][21][22][23]. The effect of dry systems (nitrogen atmosphere) versus those run in an open atmosphere was also tested and a similar rate of reaction was obtained (Table 1, entry 25).…”
Section: Resultsmentioning
confidence: 92%
“…Cur-rently one of the great challenges in the development of new synthetic methodologies is the use of the most environment-friendly conditions. [20][21][22] As alternatives, several sustainable approaches for the synthesis of heterocycles, using transition metal-free conditions, have been reported. [23][24][25][26][27] In this paper, we reported an inexpensive and environmentally friendly synthetic method for the synthesis of benzothiazolo derivatives 3 or 4 using a Lewis acid-promoted reaction of benzoimidazole thiols with propargyl alcohol derivatives (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkynes are a powerful type of dipolarophiles in versatile cycloadditions reactions. Among them, 2-alkynoates have been frequently utilized in [3 + 2] cycloaddition reactions with 1,3-dipoles to produce a myriad of heterocycles such as pyrroles, pyrazoles, and triazoles (Scheme a). In sharp contrast, the use of 3-alkynonates in cycloaddition reactions is still in its complete infancy. In fact, 3-alkynoates could be easily prepared from terminal alkynes and diazoacetates under simple conditions, whereas their synthetic potential did not receive much attention.…”
Section: Introductionmentioning
confidence: 99%
“…and reducing possible toxicity concerns. The increasing presence of various aromatic heterocycles in drugs is no doubt related to advances in synthetic methodology such as metal-catalyzed cross-couplings, 1a hetero-couplings, 1b and metal-free conditions, 1c d enabling rapid access to a wide variety of functionalized heterocyclic scaffolds.…”
mentioning
confidence: 99%